CPSU and CSC conference report - Smith, Mike (CPSU [London]GB, 2009)
Considers how and in what ways actors could reform international institutions to make global coordination fairer and more effective. Deals with the reform of the Commonwealth; the reform of international institutions and the role of the Commonwealth; and, ensuring a voice for smaller states.